2017
DOI: 10.1002/2017jd026626
|View full text |Cite
|
Sign up to set email alerts
|

A cautionary tale: A study of a methane enhancement over the North Sea

Abstract: Airborne measurements of a methane (CH4) plume over the North Sea from August 2013 are analyzed. The plume was only observed downwind of circumnavigated gas fields, and three methods are used to determine its source. First, a mass balance calculation assuming a gas field source gives a CH4 emission rate between 2.5 ± 0.8×104 and 4.6 ± 1.5×104 kg h−1. This would be greater than the industry's reported 0.5% leak rate if it were emitting for more than half the time. Second, annual average UK CH4 emissions are com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 55 publications
2
17
0
Order By: Relevance
“…An alternate explanation would assign a broad elevated baseline concentration to the offshore source(s) plus an additional unknown local emission event at closer range. This mixed source hypothesis parallels recent studies of a North Sea offshore plume, much bigger in both spatial extent and measured flux, where methane isotope ratios suggested a mixture of oil and gas and other sources (Cain et al, 2017). With the current information currently available no robust conclusions can be drawn.…”
Section: Offshore Emissionssupporting
confidence: 80%
“…An alternate explanation would assign a broad elevated baseline concentration to the offshore source(s) plus an additional unknown local emission event at closer range. This mixed source hypothesis parallels recent studies of a North Sea offshore plume, much bigger in both spatial extent and measured flux, where methane isotope ratios suggested a mixture of oil and gas and other sources (Cain et al, 2017). With the current information currently available no robust conclusions can be drawn.…”
Section: Offshore Emissionssupporting
confidence: 80%
“…Methane emitted by organic waste is enriched as a result of methane oxidation after its production in the anoxic layer. Here, a value of −52 ‰ was used, in agreement with Chanton et al (1999) (−58 ‰ to −49 ‰) and close to what was found by Bergamaschi et al (1998) (−55 ‰). The emissions of those two sources are an order of magnitude lower than anthropogenic emissions from fossil fuel production; thus, their isotopic signature does not significantly impact the isotopic signal at observation sites.…”
Section: Source Isotopic Signaturessupporting
confidence: 84%
“…This increase is largely driven by anthropogenic activities though uncertainties exist in the magnitude of individual source sectors and sinks (Turner et al, 2019). Observatories have been set up around the world to track trends in CH 4 concentrations (de Coninck et al, 2018).…”
Section: Introductionmentioning
confidence: 99%